Developing Religious Character in Santri with Special Needs at Pesantren - Amrulloh, Moch. Bachrurrosyady; Awwaliyah, Saskia Nabilah (Academia Publication, 2023)
This study aimed to explore the process of religious character development in students with special needs and identify the specific religious traits developed at Pondok Pesantren Salafiyyah Nurul ‘Ulum Gresik. This study was conducted using a qualitative descriptive approach, utilizing observation, interviews, and documentation for data collection. The findings showed that religious character formation in students with special needs occurred through three stages: the learning stage, the awareness formation stage, and the habit formation stage. The religious traits developed include worship (demonstrated by their ability to perform obligatory and sunnah prayers), jihad (determination, reflected in their willingness to worship, study, and help others), discipline (seen in their commitment to learning and religious practices), independence (evident in their ability to manage daily tasks without relying on others), and social care (shown through their concern for others and the environment.